2022
DOI: 10.1021/acsomega.2c03536
|View full text |Cite
|
Sign up to set email alerts
|

Well-Tempered Metadynamics Simulations Predict the Structural and Dynamic Properties of a Chiral 24-Atom Macrocycle in Solution

Abstract: Inspired by therapeutic potential, the molecular engineering of macrocycles is garnering increased interest. Exercising control with design, however, is challenging due to the dynamic behavior that these molecules must demonstrate in order to be bioactive. Herein, the value of metadynamics simulations is demonstrated: the free-energy surfaces calculated reveal folded and flattened accessible conformations of a 24-atom macrocycle separated by barriers of ∼6 kT under experimentally relevant conditions. Simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
(65 reference statements)
2
15
0
Order By: Relevance
“…This situation could not be dismissed readily as the result of constraints imposed by cyclization. Computational models using well-tempered metadynamics suggested that these macrocycles can adopt multiple conformations [ 26 ]. The physical manipulation of Corey–Pauling–Koltun models corroborated these conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…This situation could not be dismissed readily as the result of constraints imposed by cyclization. Computational models using well-tempered metadynamics suggested that these macrocycles can adopt multiple conformations [ 26 ]. The physical manipulation of Corey–Pauling–Koltun models corroborated these conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, variable-temperature NMR experiments reveal markedly different behavior among this series of macrocycles. We have reported that G-G moves between two folded, enantiomeric states 48 by way of an extended structure. 49 Importantly, these two states interconvert the axial and equatorial positions of α-H, B and C protons much like the ring-flip in cyclohexane.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… [37–40] The synthesis and characterization of 1 has been described [38] . The preparation of 2 follows the same route [38] …”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40] The synthesis and characterization of 1 has been described. [38] The preparation of 2 follows the same route. [38] Briefly, the monomers are obtained in two steps starting with the one-pot, sequential substitution of trichlorotriazine to yield the carboxylic acid intermediate.…”
Section: Synthesis and Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation